ANTIBACTERIAL EFFECTS OF ETHANOL EXTRACT OF GREEN TEA (Camellia Sinensis) ON STAPHYLOCOCCUS AUREUS BACTERIA - Dwi Septian Wijaya (Journal of Holistic and Traditional Medicine, 2021)
The Indonesian state is known for its rich natural resources. Tea is one of the natural resources in Indonesia and is the beverage ofchoice for consumption by the public. Tea also has a refreshing and comfortable effect. Phytochemical examination of tea showsthe presence of compounds such as alkaloids, saponins, tannins, catechins, and polyphenols. Another component of tea, namelypolyphenols, can have a pharmacological effect on a person. The polyphenols in tea also have many biological effects in humans,ranging from their effects as antioxidants, anti-aging, anti-cancer, anti-dental caries, and antibacterial. Staphylococcus aureus is anopportunistic pathogen that colonizes the surface of the skin and mucosa of individuals. These bacteria are capable of causing awide spectrum of diseases in humans starting from diseases caused by toxins, such as toxic shock syndrome, to deadly diseasessuch as septicemia, endocarditis, pneumonia, and osteomyelitis.